2009
DOI: 10.1177/1352458509106636
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s syndrome myelopathy: spinal cord involvement in Sjögren’s syndrome might be a manifestation of neuromyelitis optica

Abstract: All patients with SSM had poor prognosis with high mean annual relapse rates, and most seemed to have the clinical and immunological characteristics of NMO. Early aggressive immune therapies should be considered in patients with SSM irrespective of the presence or absence of optic neuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 19 publications
1
55
0
5
Order By: Relevance
“…These findings raise the question of whether an association exists between NMO and the CNS disease seen in SS. The small number of patients in our series precludes firm conclusions; however, additional studies have reported a similar association (8,30,39). Definitive evidence for an association between NMO and SS has not yet been established, and mechanistic studies are needed to explain the potential connection between the 2 diseases.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These findings raise the question of whether an association exists between NMO and the CNS disease seen in SS. The small number of patients in our series precludes firm conclusions; however, additional studies have reported a similar association (8,30,39). Definitive evidence for an association between NMO and SS has not yet been established, and mechanistic studies are needed to explain the potential connection between the 2 diseases.…”
Section: Discussionmentioning
confidence: 62%
“…LM is a characteristic finding in NMO/NMOSD and its presence may be used to differentiate from myelitis in classic MS, which rarely extends beyond a single vertebral segment (33). Longitudinal cord involvement has been reported in SLE and SS as well (7,8,14,17,22,23,30,34,35). These reports have identified a high prevalence of the NMO-IgG antibody and additional features consistent with concurrent NMO/NMOSD in these patients.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Additional cases describing the co-occurrence of Sj€ ogren syndrome with NMO were reported prior to the general availability of the anti-AQP4 antibody assay (Mochizuki et al, 2000;Arabshahi et al, 2006;Gokcay et al, 2007). Subsequent to the commercial availability of the anti-AQP4 antibody test, multiple cases of Sj€ ogren syndrome-associated myelopathy have tested seropositive for the anti-AQP4 antibody (Hamnik et al, 2008;Javed et al, 2008;Sofat and Venables, 2008;Kim et al, 2009;Min et al, 2009;Wandinger et al, 2010;Kahlenberg, 2011). As with SLE, there appears to be overlap between NMO and Sj€ ogren syndrome.…”
Section: Sjö Gren Syndromementioning
confidence: 99%